Hiking Wyoming : a guide to the state's greatest hiking adventures - Hunger, Bill; Dawson, Ben; Dawson, Roxy (Falcon guide., 2022)
"Hiking Wyoming features concise descriptions and detailed maps for 48 easy-to-follow trails throughout the state that allows hikers of all levels to enjoy adventurous views and experience the grandeur of Wyoming. Readers will explore hidden gems and popular hikes in the Laramie Range, Sherman Mountains, Big Horn Mountains, Wind River Range, the Washakie Wilderness, Bearooth Mountains, Grand Teton National Park, and epic trails in between. Discover trails suited to every ability that will thrill beginners and experts alike" --